Child Language Acquisition : Contrasting Theoretical Approaches / [electronic resource] - Ambridge, Ben; Lieven, Elena V. M. (Cambridge : Cambridge University Press, 2011)
Is children's language acquisition based on innate linguistic structures or built from cognitive and communicative skills? This book summarises the major theoretical debates in all of the core domains of child language acquisition research (phonology, word-learning, inflectional morphology, syntax and binding) and includes a complete introduction to the two major contrasting theoretical approaches: generativist and constructivist. For each debate, the predictions of the competing accounts are closely and even-handedly evaluated against the empirical data. The result is an evidence-based review of the central issues in language acquisition research that will constitute a valuable resource for students, teachers, course-builders and researchers alike.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Language acquisition; Language arts (Early childhood); Verbal ability in children